Menstrual Hygiene in Adolescent Girls: Findings from a Survey in the Urban Government Schools, Visakhapatnam, India - Vandana Valluri; Saivaishnavi Attili; Phani Krishna Chamarty; Tejaswi Prabhanjana; Murali Santosh (Preventive Medicine: Research & Reviews, 2025)
Background: Menstrual health management is influenced by social and cultural factors, as well as knowledge gaps. Poor hygiene practices can negatively affect academic performance and health outcomes. Materials and Methods: A survey was conducted among 1350 adolescent girls in urban public schools in Visakhapatnam, India. Results: The survey found positive progress in menstrual hygiene management, but some challenges remain. While 81.7% of girls reported having enough sanitary materials, only 66.1% had access to soap and water for hygiene purposes. Over half (52.4%) of the students struggled with menstrual pain, and 37.6% reported difficulty participating in school activities during their periods. Notably, 93.5% of the respondents were unaware of the human papillomavirus vaccine and its ability to prevent cervical cancer. Conclusions: This survey highlights progress in menstrual hygiene management in urban schools, and also identifies persistent knowledge gaps and access issues.